Anthropology of Smells: History and Modernity - Avakyan, Laura; Golubeva, Svetlana; Tsimmerman, Galina; Shcherbakov, Vladimir (Տիգրան Մեծ)
The smell is one of the most significant factors influencing human consciousness and behaviour. This is due not only to the biological aspects of its origin and the actualization of the bodily being of a human but also to deeply rooted in culture and society stereotypes and patterns of perception that determine the value system, cognitive attitudes and social structure of each particular culture. This is the essence of the relevance of the project of historization and anthropologization of smell, based on the original model of describing the transformation of human cultural practices, which equally takes into account the natural and social aspects of human life and can identify the regulatory mechanisms, order and principles of sociocultural changes. Although a modern man does not fully realize the power of olfactory area of his sense empire, this does not free him from the power of reflex reactions, cultural norms and social demarcations, originating in the olfactory receptivity. Perhaps, that is why the rationalistic ideal of deodorization has not been achieved by modern perfumers, who only mask, but not destroy smells, that are, in some sense, completely indestructible, because they can effectively shape a person‟s cultural identity, historical memory and even self-awareness.
Keywords: Social philosophy